Lack of transfer of skills after virtual reality simulator training with haptic feedback. - Våpenstad, Cecilie; Hofstad, Erlend Fagertun; Bø, Lars Eirik; Kuhry, Esther; Johnsen, Gjermund; Mårvik, Ronald; Langø, Thomas; Hernes, Toril Nagelhus (Minimally Invasive Therapy & Allied Technologies, 2017)
Background and objective:Virtual reality (VR) simulators enrich surgical training and offer training possibilities outside of the operating room (OR). In this study, we created a criterion-based training program on a VR simulator with haptic feedback and tested it by comparing the performances of a simulator group against a control group. Material and methods:Medical students with no experience in laparoscopy were randomly assigned to a simulator group or a control group. In the simulator group, the candidates trained until they reached predefined criteria on the LapSim®VR simulator (Surgical Science AB, Göteborg, Sweden) with haptic feedback (XitactTMIHP, Mentice AB, Göteborg, Sweden). All candidates performed a cholecystectomy on a porcine organ model in a box trainer (the clinical setting). The performances were video rated by two surgeons blinded to subject training status. Results:In total, 30 students performed the cholecystectomy and had their videos rated (N = 16 simulator group,N = 14 control group). The control group achieved better video rating scores than the simulator group (p < .05). Conclusions:The criterion-based training program did not transfer skills to the clinical setting. Poor mechanical performance of the simulated haptic feedback is believed to have resulted in a negative training effect.